Effect of a polyphenol-rich dietary supplement containing Pinus massoniana bark extract on blood pressure in healthy adults: A parallel, randomized placebo-controlled trial - Jessica J.A. Ferguson; Christopher Oldmeadow; David Bentley; Shaun Eslick; Manohar L. Garg (Elsevier, 2022)
Objectives: High blood pressure (BP) is a major risk factor for cardiovascular disease and prevalence rates continue to rise with ageing populations. Polypharmacy remains a burden among the ageing, thus alternative effective strategies are warranted. This study investigated the effects of a polyphenols rich dietary supplement containing Pinus massoniana bark extract (PMBE) for modulating BP in healthy Australian adults. Design: This study is a secondary analysis of data from a double-blinded, placebo-controlled clinical trial. Methods: Sixty-two healthy adults aged 55-75 years were randomized to receive 50 mL dietary supplement containing placebo (0 mg PMBE) or PMBE (1322 mg PMBE) daily for 12 weeks. Seated systolic BP (SBP) and diastolic (DBP) were measured at baseline, 6 weeks and 12 weeks. Effects of PMBE on modulating BP was also explored in this study stratified for SBP status (optimal v high) as well as by SBP medication status. Mixed effect regression modelling was employed involving fixed categorical effects for elapsed time, treatment assignment and their interaction as well as random subject-level intercept to account for within-subject correlations resulting from repeated measurements. Significant models were further examined by addition of covariates and power calculations were performed since this study was a secondary analysis. Results: SBP significantly reduced (−3.29 mmHg, p = 0.028) after PMBE at 12 weeks compared to baseline. SBP in individuals with normal-high SBP (>120 mmHg) in the PMBE group reduced by − 6.46 mmHg (p = 0.001) at 12 weeks compared to baseline. No significant changes were reported for individuals with optimal (≤120 mmHg) SBP nor did DBP significantly change in either study groups. In individuals with non-medicated normal-high SBP, SBP significantly reduced by − 7.49 mmHg (p = 0.001) and DBP by − 3.06 mmHg (p = 0.011) at 12 weeks compared to baseline after PMBE. Cross-group comparisons were not statistically different. Conclusions: A polyphenol-rich dietary supplement derived from PMBE led to a clinically and statistically significant reduction in SBP in adults. Future studies to investigate the effects of PMBE-polyphenol supplementation on BP are warranted to confirm and explore optimal dose and impact on hypertension.